Satisfaction of patients with health care services in tertiary care facilities of Riyadh, Saudi Arabia: A cross-sectional approach - Aljarallah, Nasser Ali; Almuqbil, Mansour; Alshehri, Sultan; Khormi, Amro Mohammed Sawadi; AlReshaidan, Reshaidan Mohammed; Alomran, Fayez Hadi; Fawzan Alomar, Nasser; Alshahrani, Fayez Faleh; Alshammari, Majed Sadun; Alsanie, Walaa F.; Alhomrani, Majid; Alamri, Abdulhakeem S.; et al. (Frontiers in Public Health, 2023)
As part of Saudi Vision 2030, the country's healthcare system is undergoing a significant makeover, with accessibility and effectiveness serving as the benchmarks for measuring patient care quality. This study's goal was to ascertain the degree of patient satisfaction with the medical care and services received in Riyadh's tertiary care facilities. The PSQ-18 (Patient Satisfaction Questionnaire-18), a standardized validated questionnaire including areas of "overall satisfaction," "technical quality," "interpersonal aspect," "communication," "financial aspect," "time spent with the doctor," and "accessibility and convenience," was used in this cross-sectional study on 384 patients of two tertiary care facilities in Riyadh, Saudi Arabia, over a 6-month period. The degree to which sociodemographic characteristics and components of patient satisfaction are correlated was assessed using binary and multiple regression analysis. When the P value was less than 0.05, the results were considered significant and were presented as adjusted odds ratios (AOR). To ascertain how each PSQ-18 subscale affected other subscales, a Pearson Correlation analysis was conducted. The overall degree of satisfaction with all 18 items was 73.77%. The financial component received a rating of 81% compared to 77% for general satisfaction. Technical quality (75%) was followed by accessibility and convenience (73.5%), communication (73%) and interpersonal elements (72%). At 68%, the time spent in the doctor's domain received the lowest rating. The odds of satisfaction were increased by 3.87 times, 3.45 times, and 3.36 times among those who are employed, qualified by university education, and married compared to unemployed (P value = 0.018), less qualified (P value = 0.015) and singles (P value = 0.026), respectively. Male gender and younger age group also made 1.61 and 1.78 times more of a difference in higher satisfaction ratings. The general satisfaction domain showed a positive association with other areas. Participants who were satisfied with the communication and accessibility and convenience domains of healthcare providers were the only ones who were typically satisfied with the domain of doctor time spent. The study's findings could act as a benchmark for Saudi Arabia's healthcare services as well as a starting point for quality assurance procedures.